TEKEVLER?MADEN (ELAZIĞ) ARASI SAHANIN FLORASI - ÇAKILCIOĞLU, UĞUR (Fırat Üniveristesi, 2008)
Bu araştırma 2005-2007 yılları arasında Tekevler - Maden ilçesi (Elazığ) arası sahada gerçekleştirilmiştir. Bu süre içerisinde 3191 bitki örneği toplanmıştır. Bu örneklerin adlandırılmasından sonra, 67 familya, 304 cins ve 577 tür ve tür altı seviyede takson saptanmıştır. Araştırma alanından saptanan 577 taksonun 1'i Pteridophyta, 576'si Spermatophyta bölümlerindendir. Spermatophyta'ya ait taksonların 2'si Coniferophyta, geriye kalan 574'ü Magnoliophyta alt bölümündedir. Magnoliophyta'ya ait 574 taksonun 511'i Magnoliopsida, 63'ü Liliopsida sınıflarında yer almaktadır. Araştırma alanından saptanan 57 takson (% 9.9) Türkiye için endemiktir. Taksonların bitki coğrafyası bölgelerine dağılım oranları şöyledir: İran-Turan elementleri 204 (% 35.4), Avrupa-Sibirya elementleri 30 (% 5.2), Akdeniz elementleri 28 (% 4.9).En büyük on familya ve takson sayıları şöyledir. Asteraceae 98, Fabaceae 62, Lamiaceae 50, Brassicaceae 39, Caryophyllaceae 36, Poaceae 35, Apiaceae 27, Boraginaceae 24, Rosaceae 23, Ranunculaceae 19. En büyük on cins ve takson sayıları şöyledir: Astragalus 11, Trifolium 10, Silene 9, Euphorbia 9, Alyssum 9, Centaurea 9, Salvia 8, Veronica 7, Vicia 7, Ranunculus 7.Anahtar kelimeler: Flora, Türkiye, Elazığ, Maden, Tekevler, Endemik.

This research was carried out in Tekevler and Maden district located (Elazığ) between 2005-2007. 3191 plant specimens were collected in this period. After the identification of these specimens, 67 families, 304 genera and 577 level of species, subspecies and variates taxa were determined. One out of the 577 taxa determined in the research area belong to Pteridophyta division, the remaining 576 taxa belong to Spermatophyta division. Two taxa belong to Coniferophyta subdivision, the remaining 574 taxa were Magnoliophyta subdivision which belongs to Spermatophyta division. 63 taxa were in the Liliopsida class and 511 taxa were Magnoliopsida class each of which belongs to Magnoliophyta subdivision. 57 taxa determined in the research area (% 9.9) were endemic for Turkey. The scattering ratios of the taxa to the phytogeographic regions were as follows: Irano-Turanian elements 204 (% 35.4), Euro-Siberian elements 30 (% 5.2), Mediterranean elements 28 (% 4.9).The largest ten families and taxon numbers were as follows: Asteraceae 98, Fabaceae 62, Lamiaceae 50, Brassicaceae 39, Caryophyllaceae 36, Poaceae 35, Apiaceae 27, Boraginaceae 24, Rosaceae 23, Ranunculaceae 19. The largest ten genera and taxon numbers are as follows: Astragalus 11, Trifolium 10, Silene 9, Euphorbia 9, Alyssum 9, Centaurea 9, Salvia 8, Veronica 7, Vicia 7, Ranunculus 7.Keywords: Flora, Turkey, Elazığ, Maden, Tekevler, Endemic.
The flora of area between Tekevler and Maden (Elaziğ)
Keywords: Botanik